Identification of the novel allele, HLA-C*01:136 in a German cord blood donor originating from Azerbaijan - Zingsem, Jürgen; Hauck-Dlimi, Barbara; Dullinger, Katharina; Weisbach, Volker Günter; Strobel, Julian (HLA, 2018)
HLA-C*01:136 identified by next generation sequencing and confirmed by Sanger sequencing.
EVALuna2:213431